Review Article: Investigating the Delay Factors of Construction Projects Using Narrative Analysis Approach (Iraqi Journal of Civil Engineering, 2022)
Construction delays are common problems in civil engineering projects in Arab countries. Because of the importance of this problem, the study reviewed many studies that dealt with the topic of delay in the construction projects of their countries.The study included the delay in projects in Iraq. Jorden, Palestine, Saudi Arabia, United Arab Emirates, Qatar, Yemen, Egypt, Sudan, Algeria and Morocco. The projects included infrastructure facilities, public buildings, housing complexes, water treatment plants, sports facilities, water supply, roads. Quantitative method via a structured questionnaire was implemented in all these studies, the questionnaires were distributed to experienced project parties such as the owner, contractor, consultant and other parties. The relative importance method was used to analyze the results of the questionnaire to obtain the highest ten or five factors with the highest rank which cause delay. The results showed that the groups of contractor and owner has the highest percentage and were repeated several times compared to the rest of the groups.The top five factors causing delay of construction projects in Arab countries are, problems of cash flow and ﬁnancial by owner, difficulties in financing the project by the contractor, Poor site management and supervision of the contractor, selecting the contractor who has the lowest bid and ineffective planning and scheduling by contractors